Mid-gap photoluminescence and magnetic properties of GaMnN films grown by metal-organic chemical vapor deposition - 邢海英 徐章程 崔明启 谢玉芯 张国义 (Chinese physics B, 2014)
Metal-organic chemical vapor deposition （MOCVD） grown ferromagnetic GaMnN films are investigated by photo- luminescence （PL） measurement with a mid-gap excitation wavelength of 405 nm. A sharp PL peak at 1.8 eV is found and the PL intensity successively decreases with the addition of Mn, in which the Mn concentration of sample A is below 1% （[Mn]A =0.75%） but its PL intensity is stronger than other samples＇. The 1.8-eV PL peak is attributed to the recombination of electrons in the t2 state of the neutral Mn3＋ acceptor with holes in the valence band. With Mn concentration increasing, the intensity of the PL peak decreases and the magnetic increment reduces in our samples. The correlation between the PL peak intensity and ferromagnetism of the samples is discussed in combination with the experimental results.